2015
DOI: 10.1039/c5ra01401h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of migration of layered nanoparticles during melt blending on the phase morphology of poly (ethylene terephthalate)/polyamide 6/montmorillonite ternary nanocomposites

Abstract: To study the effect of migration and selective localization of layered nanoparticles during melt compounding on the phase morphology of polymer blends, poly (ethylene terephthalate) (PET)/ polyamide 6 (PA6)/organic montmorillonite (OMMT) ternary nanocomposites were prepared. Three different blending sequences were adopted either by pre-compounding OMMT into PET or into PA6 or by mixing all three components together. The morphology and tensile properties of PET/PA6/OMMT nanocomposites were investigated. TEM obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
(45 reference statements)
4
14
0
Order By: Relevance
“…Therefore, blending of PA6 with PET offers an interesting way to obtain a new material with promising property and low cost. Essentially, blends of PA6 and PET are immiscible and exhibit poor interfacial adhesion and low mechanical properties . In order to improve compatibility and mechanical properties of PA6 blends, effective compatibilizers including EPR‐ g ‐MA, ethylene‐propylene‐diene monomer (EPDM), glycidyl methacrylate (GMA)‐grafted poly(ethylene‐octene) (POE‐ g ‐GMA), and their derivatives (e.g., SEBS‐ g ‐maleic acid anhydride and EPDM‐ g ‐maleic acid anhydride) are often applied for PA6 blends.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, blending of PA6 with PET offers an interesting way to obtain a new material with promising property and low cost. Essentially, blends of PA6 and PET are immiscible and exhibit poor interfacial adhesion and low mechanical properties . In order to improve compatibility and mechanical properties of PA6 blends, effective compatibilizers including EPR‐ g ‐MA, ethylene‐propylene‐diene monomer (EPDM), glycidyl methacrylate (GMA)‐grafted poly(ethylene‐octene) (POE‐ g ‐GMA), and their derivatives (e.g., SEBS‐ g ‐maleic acid anhydride and EPDM‐ g ‐maleic acid anhydride) are often applied for PA6 blends.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by (i) the higher affinity (Elias et al, 2007 andJarnthong et al, 2012) between PE and ZSM5 compared to that of TPS and ZSM5 and (ii) the decrease in viscosity of TPS dispersed phase (Xu, Qin, Yu, Huang, Zhang, & Ruan, 2015) after incorporation of ZSM5.…”
Section: Phase Morphology Of Pe/tps/zsm5 Compositesmentioning
confidence: 99%
“…It was found that compounding with ZSM5 decreased the viscosity of TPS while increased the viscosity of PE. The decrease in viscosity of TPS facilitates 16 the breakup of TPS/ZSM5 droplets (Xu et al, 2015) during mixing with PE in a twin-screw extruder. During this step, migration of ZSM5 from TPS dispersed phase to PE matrix also occurred due to the affinity between ZSM5 and PE, further leading to smaller TPS dispersed domains obtained in SII composites (Figs.…”
Section: Rheological Behavior Of Pre-mixed Pe/zsm5 and Tps/zsm5 Compomentioning
confidence: 99%
“…10,14,15 In some cases, the increase of domain size has been correlated to the selective localization of the nanollers in the minor phase and the increase of the viscosity of this phase with respect to the major phase. 10,[25][26][27] Kong et al noted that when nanosilica lled domains of polyamide 6 (PA6) are sheared inside a polystyrene (PS) matrix at high shear rates, there is a morphology renement; however, when the PA6/ nanosilica domains are subjected to low shear rate, coarsening of the domains is observed. This was attributed to the bridging effect of the nanosilica particles localized at the interface of the blends, and to the breakup suppression due to the increase of viscoelasticity and yield stress of the PA6/ nanosilica domains.…”
Section: Introductionmentioning
confidence: 99%